Long term effects of smoke inhalation in survivors of the King's Cross underground station fire. Issue 12 (December 1991) - Fogarty, P W; George, P J; Solomon, M; Spiro, S G; Armstrong, R F
Abstract : BACKGROUND: In most accidents causing smoke inhalation only a few victims actually inhale the smoke. The fire at King's Cross provided an opportunity to assess the long term effects of smoke inhalation in a larger number of patients. METHODS: Fourteen survivors from the King's Cross underground station fire were assessed for respiratory disability six months after the disaster and 10 were reassessed at two years. All had inhaled substantial quantities of smoke and 10 had skin burns of differing severity. RESULTS: Six months after the fire nine survivors admitted to one or more symptoms, which included hoarseness (two cases), cough (five cases), and breathlessness (six cases); and a survivor with asthma noted a worsening of his symptoms. The remaining five denied new symptoms. Peak expiratory flow, spirometric indices, and transfer factor for carbon monoxide were within the predicted normal ranges. The mean residual volume, however, was greater than the predicted value and the mean maximum expiratory flow at 25% of vital capacity (V25) less than predicted, with no significant differences between smokers (n = 7) and non-smokers (n = 7). At least one of these ventilatory defects, suggesting small airways obstruction, was present in 11 survivors at six months and they had persisted in the seven patients who were reassessed at two years. CONCLUSION: Smoke inhalation may be associated with injury to the small airways.